Remdesivir-Related Cardiac Adverse Effects in COVID-19 Patients: A Case-Control Study - Abedipour, Fatemah; Mirzaei, Hossein Hadavand; Ansari, Hossein; Ehsanzadeh, Neda; Rashki, Amin; Vahedi, Mohammad Mahdi; Rashki, Asma (Drug Research, 2024)
Background There have been reports of serious side effects of Remdesivir, including cardiovascular complications. The present study aimed to determine the adverse cardiovascular effects of Remdesivir and the factors affecting them in COVID-19 patients.Methods The patients were classified into two groups: those receiving Remdesivir without cardiac complications and those receiving Remdesivir with cardiovascular complications. After reviewing the patientʼs medical records, the relationship of some factors with the incidence of adverse cardiovascular effects was measured.Results Chi-square test showed that the distribution of complications in men was significantly higher than in women (P=0.001). The independent t-test revealed that the mean age in the group with complications was significantly higher than the group without complications (P=0.013). Fisherʼs exact test demonstrated a significant relationship between smoking and cardiovascular complications (P=0.05). According to the Mann-Whitney test, a significant difference was found in the mean changes of Bilirubin (P=0.02) and ALKP (P=0.01) before and after treatment in the groups with and without heart complications.Conclusion Our findings indicated that most of the COVID-19 patients suffered from sinus bradycardia, and the distribution of complications was more pronounced in men than in women. The mean age in the group with complications was higher than the group without complications. Smoking was found to be associated with the occurrence of cardiovascular complications and the mean changes of Bilirubin and ALKP before and after treatment were significantly different in the groups with and without cardiovascular complications.
Keywords: remdesivir; cardiovascular system; side effects; COVID-19